2020
DOI: 10.1017/ice.2020.1257
|View full text |Cite
|
Sign up to set email alerts
|

Scalable in-hospital decontamination of N95 filtering face-piece respirator with a peracetic acid room disinfection system

Abstract: Background: Critical shortages of personal protective equipment especially N95 respirators during the COVID- 19 pandemic continues to be a source of concern. Novel methods of N95 filtering facepiece respirator decontamination that can be scaled-up for in-hospital use can help address this concern and keep HCWs safe. Methods: A multidisciplinary pragmatic study was conducted to evaluate the use of an ultrasonic room high-level disinfection system (HLDS) that generates aerosolized peraceti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…In their study, Cutts et al demonstrate that dry fogging with PAA completely inactivated SARS-CoV-2 on test surfaces. They also suggested that with the ease of use, low cost, and overall effectiveness of a PAA, dry fogging should also be considered for decontamination in the prevention of COVID-19 (13). Another study demonstrated the effectiveness of PAA for disinfection of Geobacillus stearothermophilus (G. stearothermophilus) spores and bacteriophage MS2 on N95 respirators, proposing a PAA room disinfection system as a solution for decontamination of a great number of N95 respirators during the outbreak of COVID-19 (14).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Cutts et al demonstrate that dry fogging with PAA completely inactivated SARS-CoV-2 on test surfaces. They also suggested that with the ease of use, low cost, and overall effectiveness of a PAA, dry fogging should also be considered for decontamination in the prevention of COVID-19 (13). Another study demonstrated the effectiveness of PAA for disinfection of Geobacillus stearothermophilus (G. stearothermophilus) spores and bacteriophage MS2 on N95 respirators, proposing a PAA room disinfection system as a solution for decontamination of a great number of N95 respirators during the outbreak of COVID-19 (14).…”
Section: Discussionmentioning
confidence: 99%
“…Using the Altapure AP-4 aHP with peracetic acid, John et al found that H2O2 had dissipated to 0.0 ppm within 60 minutes of off-gassing and the peracetic acid was undetectable within 20 minutes. 13 Unpublished data by Derr et al found that H2O2 was less than <0.5 ppm, within permitted levels, after treatment. However, many aHP solutions contain silver cations or peracetic acid, requiring additional studies to determine if any toxic residues or off-gassing post-decontamination could cause harm to the wearer (Derr, Unpublished Data).…”
Section: Discussionmentioning
confidence: 92%
“… 12 John et al found that with the Altapure AP-4 aHP system with peracetic acid (Altapure, Mequon, WI), both hydrophobicity and filtration efficiency were retained following 5 cycles of decontamination. 13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research [6,7] also analyzed the effect of fogging on various surfaces (walls, floors, components of subway cars), and in work [3], a largescale application of fumigation in the urban space affecting spaces in the environment was proposed. The literature also includes many items describing the use of fogging for disinfecting medical masks and protective clothing in fumigation rooms or lodging facilities [12][13][14][15][16]. A noteworthy publication is the study by Villermaux [17], which is a very detailed analysis of atomization mechanisms.…”
Section: Introductionmentioning
confidence: 99%